Advances in Automotive Production Technology - Towards Software-Defined Manufacturing and Resilient Supply Chains Stuttgart Conference on Automotive Production (SCAP2022) - Kiefl, Niklas; Wulle, Frederik; Ackermann, Clemens; Holder, Daniel (ARENA2036, 2023)
This volume of the series ARENA2036 compiles the outcome of the 2nd Stuttgart Conference on Automotive Production (SCAP2022). The peer-reviewed contributions in this book are arranged thematically in three parts and cover a wide variety of topics: (A) Software-defined Manufacturing, (B) Data-driven Technologies, and (C) Advanced Manufacturing and Sustainability. SCAP2022 was organized by ARENA2036 in close collaboration with the Institute for Control Engineering of Machine Tools and Manufacturing Units of the University of Stuttgart. The Conference took place on site from November 16 - 18, 2022 and provided the opportunity for national and international scientists to present their latest research results. The conference has taken another big step in becoming an established forum for topics related to the production of the future. The great success of this year's conference will be continued with the next SCAP in 2024 with new forward-looking topics. This is an open access book.